Testicular Histology, Gonadal and Extragonadal Sperm Reserve of Sheep (rams) Fed Tigernut (Cyperus esculentum) Chaff and Cowpea (Vigna unguiculata L. Walp) Husk in a Mixed Ration. - Njidda, A.A.; Butswat, I.S.R.; Yakubu, H.; Chibuogwu, I.C.; Bankole, A.S. (Nigerian Journal of Animal Science, 2026)
Gonadal, extra-gonadal sperm reserves and testicular histology of Yankasa rams fed tiger nut chaff and cowpea husk in a mixed ration were studied. Thirty growing and apparently healthy Yankasa rams were randomly allotted five dietary treatments with six animals per treatment. Treatments compared were T1 (Cowpea husk 40% + Tiger nuts chaff 0%), T2 (Cowpea husk 30% + Tiger nuts chaff 10%), T3 (Cowpea husk 20% + Tiger nuts chaff 20%), T4 (Cowpea husk 10% + Tiger nuts chaff 30%), and T5 (Cowpea husk 0% + Tiger nuts chaff 40%). The testicular morphometry and gonadal and extra-gonadal sperm reserves showed significant differences (P<0.05) in all the parameters observed. For testicular morphometry, the weight and length of the right testes for T1 were highest (180 g) and (13 cm) and least for T5 (38 g) and (7cm) 1 5 respectively. A similar trend was observed for the weight and length of the left testes as 175 g and 12cm, and 39 g and 7cm respectively. Based on the result of this investigation, testicular morphometry, gonadal, and extra-gonadal sperm reserves of rams fed 40% cowpea husk and 0% tiger nuts chaff mixed ration were of the best value. However, semen from animals fed a mixed ration of cowpea husk should be further investigated to determine the impact on the fertility of breeder rams.